Effect of Diazinon on Reproductive System of Adult Male Mice - Al- Attabi, Mohammad Rjy; Hussain, Sahib M.; Al-Okaily, Baraa N. (Journal of Kerbala for Agricultural Sciences, 2017)
This study was designed to investigate the effect of diazinon on reproductive system of adult male mice reproductive performance. Forty adult male albino mice were randomly divided into two equal groups. Collars made to the mice that were caged alone. The animals of the first group were dipped in tap water without of diazinon and served as control group, while the animals of the second group were dipped with diazinon 60% in dilution (1-1000) and used as treated group. Five animals from each group were sacrificed on the days 1, 14, 28 and42 after the end of treated period. The results revealed that there were significant decrease in sperm count, sperm motility, serum testosterone concentration and diameter and thickness of seminiferous tubules. These results associated with significant increase in dead and abnormal sperm. The activity of acetylcholinesterase was significantly decreased at the first day of post treated period. Histopathological examination of the testes also revealed degenerative changes in the cell lining the seminiferous tubules. In conclusion, diazinon had adverse effect on the reproductive system of adult male mice may be occurrence of oxidative stress.